(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2016)
Rheumatoid arthritis is the chronic painful disease of joint destruction and functional disability needing immediate action with patient compliance. Pain relieving Quick dissolving film (QDF) will be an accurate patient acceptable solution for this condition. Lornoxicam (LXM) is a non-steroidal anti-inflammatory drug (NSAID) with half life 3-5 hours, complete absorption from GIT (90-100%) having advantage from a tolerability standpoint. LXM has bitter taste thus to improve the palatability, the drug was complexed with Beta Cyclodextrin in different ratios using kneading method by optimizing the kneading time. Taste evaluation was done by human volunteer and UV method. The optimized drug-beta cyclodextrin complex was incorporated in QDF by solvent casting technique using PVA: Pullulan as polymers and PEG 400 as plasticizer. The optimization of concentration of PVA: Pullulan and PEG 400 was done by 32 factorial design to observe its effect on disintegration time, drug release in 20 minutes, tensile strength and folding endurance as dependent variable. The optimized batch QDF1 gave disintegration in 22 second and 98 % drug release in 20 minutes with suitable strength and flexibility. It can be concluded that the development of Quick dissolving film of Lornoxicam could give quick relief from the pain of rheumatoid arthritis with greater compliance compared to other conventional dosage forms.